THEORETICAL BASIS OF THE IMPLEMENTATION OF THE TURKISH EDUCATIONAL SYSTEM IN TEACHING LIGHT INDUSTRY SCIENCES - Khatamova Zumrad Nazirjonovna; Abdulazizov Otayorbek (Galaxy International Interdisciplinary Research Journal, 2023)
One of the important factors of the development of any country is, of course, the education system. Each country is responsible for quality education of its citizens. In addition to fully meeting modern standards, the education system in Turkey also has its own characteristics. If you want to know how it is taught in the state of Turkey, then the information collected by us will surely be interesting for you.